The Level of consumer confidence in the implementation of CHSE (Clean, Healthy, Safety, Environment Sustainability) hotel certification during the Covid-19 pandemic in Palembang City, Indonesia - Andi Ade Zulkifli; Pelliyezer Karo Karo; Risman Jaya (Journal of Applied Sciences in Travel and Hospitality, 2023)
This research identifies and measures hotel consumers' trust regarding the application of CHSE (clean, healthy, safety, and environmental sustainability) in three, four, and five-star hotels in Palembang during the COVID-19 pandemic. CHSE certification is a program from the Ministry of Tourism and Creative Economy of the Republic of Indonesia to increase consumer confidence in reusing hotel services. The study used direct observation techniques in restaurants and distributed questionnaires to respondents. This descriptive-analytic survey uses a questionnaire as a variable measurement scale. The research population is star hotel guests who have received CHSE certification, with a sample of 602 respondents. The study results show that respondents dominated by women, millennials, and generation Z, the choice of visiting 3-star and 4-star hotels, the purpose of visits to carry out tasks and attend events, while the phenomenon of staycation destinations began to grow during the pandemic by 17 percent. Concerning the CHSE, there was a 10.9 percent growth in confidence in implementing the CHSE with the opportunity for Covid-19 transmission. The seriousness of the implementation of CHSE has yet to meet consumers' perspectives, and only three of the thirteen indicators have met consumer expectations with an average value of 83 percent. In addition, there is a shift in consumer considerations in choosing hotels, from consumers sensitive to price and cleanliness factors. In contrast, the CHSE implementation factor has become a consideration of 51 percent of respondents.